FACTORS CONTROLLING STERILITY IN CANNED PRAWN - CHAUDTTTTRI, D R; GOPALAKRISHNA IYER, T S; PILLAI, V K (Fishery Technology, 2025)
Probable sources of contamination of raw, blanched and processed meat at various stages of handling and methods for their rectification have been described in the paper. Inter-relationship between absolute sterility and commercial sterility with particular reference to the sanitation of the factory has been discussed.